Effect of psycho-religious group therapy on hallucination in schizophrenia patient - Fahrizal, Yanuar; Saputri, Reny Nur (Universitas Muhammadiyah Purwokerto, 2023)
Background: Psycho-religious therapy can be used to treat schizophrenia patients. Group therapy is also effective at reducing the signs and symptoms of hallucinations. Combining these two methods for the intervention of schizophrenic patients who experience hallucinations still needs scientific evidence.Objective: This study aims to determine the influence of dhikr psycho-religious group therapy on changes in signs of hallucination symptoms in patients with a psychotic disorder.Methods: This is a pre-experiment study with a pre-post-test design. The sample number was 33 participants in schizophrenia patients with hallucinations. Sampling techniques use purposive sampling that meets inclusion criteria. The research instrument uses a hallucination signs and symptoms evaluation questionnaire. Dhikr psycho-religious group therapy is carried out in 4 times meetings with two stages—data analysis using frequency distribution and statistically paired t-test test.Results: The hallucination symptom score before the intervention was 22.36; after the intervention, it decreased to 11.03. The statistical analysis showed significant differences in hallucination symptoms before and after the intervention of psycho-religious group therapy (p<0.05). Psycho-religious group therapy provides a medium effect in reducing hallucination symptoms (Cohen's d: 3.09).Conclusion: Psycho-religious group therapy can significantly reduce hallucination symptoms.